2022
DOI: 10.18502/ijhoscr.v16i1.8439
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Dexamethasone plus Vincristine versus Standard Regimen in Induction Therapy of Adult Acute Lymphoblastic Leukemia Patients Undergoing Hematopoietic Stem Cell Transplantation

Abstract: Background: Current treatment options of acute lymphoblastic leukemia(ALL) include chemotherapy alone or hematopoietic stem cell transplantation (HSCT) following induction chemotherapy both along with CNS prophylaxis. The usual and standard induction regimens currently administered could have severe complications and mortality. Materials and Methods: To lessen induction regimen complications in ALL patients who undergo HSCT, we used a cytoreduction induction regimen including dexamethasone (8 mg, IV, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Thirteen publications in adult hematologic malignancies were identified describing long‐term results for busulfan/chemotherapy combination pretransplant conditioning regimens, encompassing 2076 patients, predominantly in allogeneic HCT settings 20–32 . Three additional publications described long‐term results in adults (also with hematologic malignancies) when busulfan was combined with TBI and additional chemotherapy agents, involving 744 patients 33–35 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen publications in adult hematologic malignancies were identified describing long‐term results for busulfan/chemotherapy combination pretransplant conditioning regimens, encompassing 2076 patients, predominantly in allogeneic HCT settings 20–32 . Three additional publications described long‐term results in adults (also with hematologic malignancies) when busulfan was combined with TBI and additional chemotherapy agents, involving 744 patients 33–35 .…”
Section: Resultsmentioning
confidence: 99%
“…14 Thirteen publications in adult hematologic malignancies were identified describing long-term results for busulfan/chemotherapy combination pretransplant conditioning regimens, encompassing 2076 patients, predominantly in allogeneic HCT settings. [20][21][22][23][24][25][26][27][28][29][30][31][32] Three additional publications described long-term results in adults (also with hematologic malignancies) when busulfan was combined with TBI and additional chemotherapy agents, involving 744 patients. [33][34][35] Five of the busulfan/chemotherapy publications and each of the three busulfan/TBI/chemotherapy publications involved median follow-up exceeding 5 years, summarized in Table 3; the remaining eight selected studies involved median follow-up of between 3 and 5 years, summarized in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…D/R CMV serological status remains the main risk factor influencing the incidence and mortality of CMV reactivation/disease after HSCT [ 1 , 16 , 34 , 35 ]. It has been demonstrated that seropositive recipients are more likely to experience CMV reactivation if they received a graft from a seronegative donor than from a seropositive one [ 36 , 37 , 38 ]. Nevertheless, CMV reactivation occurs in up to 70% of CMV IgG seropositive allo-recipients regardless of donor status according to some recent studies, and LMV prophylaxis is therefore recommended for all CMV seropositive recipients [ 1 , 11 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was more pronounced in cancer survivors with androgen deficiency (Greenfield et al 2010 ). Testosterone levels were below the lower level of normal in 84% of male recipients of HSCT for acute leukemia (Vaezi et al 2016 ). Hypogonadism appears to be common after HSCT (Inamoto and Lee 2017 ) and may be another explanation for the lower QoL and higher physical fatigue levels (Savani et al 2011 ) in males compared to females within our study.…”
Section: Discussionmentioning
confidence: 99%